2019
DOI: 10.3390/met9060716
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of 42SiCr-Pipes for Quenching and Partitioning by Longitudinal HFI-Welding

Abstract: In the pipe manufacturing and pipe processing industry, the demand for cost-effective pipes with high strength and good ductility is increasing. In the present study, the inductive longitudinal welding process was combined with a Quenching and Partitioning (Q&P) treatment to manufacture pipes with enhanced mechanical properties. The aim of the Q&P process is to establish a martensitic structure with increased retained austenite content. This allows for the beneficial use of both phases: the strength of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Martensite start (M S ) and martensite finish (M F ) temperatures as well as the A c3 temperature of the material can be found in literature. [ 26–29 ] These temperatures were about 300, 180, and 845 °C, respectively. The 42CrSi steel represents a modification of materials widely used in the automotive sector, in particular for the production of transport vehicle components.…”
Section: Methodsmentioning
confidence: 99%
“…Martensite start (M S ) and martensite finish (M F ) temperatures as well as the A c3 temperature of the material can be found in literature. [ 26–29 ] These temperatures were about 300, 180, and 845 °C, respectively. The 42CrSi steel represents a modification of materials widely used in the automotive sector, in particular for the production of transport vehicle components.…”
Section: Methodsmentioning
confidence: 99%
“…Poorer quality can lead to huge losses and create life-or health-threatening situations. Therefore, HFI welding processes must be designed very precisely so that the weld does not have any discontinuities (defects) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Another field of induction-based joining is the longitudinal welding of pipes from advanced high strength steels (AHSS) by high-frequency induction welding. The authors demonstrated the longitudinal welding of 42SiCr- [33] and 34MnB5-pipes [34] in combination with subsequent heat treatments to manufacture pipes with enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%